MELACAK JEJAK KOSMOPOLITANISME ACEH DI JALUR REMPAH NUSANTARA - Fakrur Razi (Yayasan An-Nur Meunara Baro, 2025)
This article revisits the cosmopolitan legacy of Aceh within the framework of the Nusantara spice route, emphasizing its strategic role as a hub of trade and cultural interaction from the 16th to the 18th century. Employing an interdisciplinary approach that integrates oral history, maritime archaeology, and philological analysis of ancient manuscripts, the study reconstructs Aceh's position as a crucial node in the global network linking the Middle East, South Asia, China, and Europe. The findings indicate that Aceh functioned not only as a spice entrepôt but also as an intellectual exchange center and home to vibrant multiethnic communities. Loanwords in the Acehnese language, Islamic literacy traditions, and traces of transregional scholars serve as evidence of the region’s once-flourishing cosmopolitan dynamics. However, the rupture of historical narratives due to colonialism, political centralization, and the lack of local historical education has contributed to the erosion of this collective memory. Therefore, this study recommends the revitalization of local historical awareness through participatory education and community-based heritage tourism. It also opens pathways for further research on Aceh’s role in cultural diplomacy and broader interregional relations in Southeast Asian history.